Camelobaetidius guaycara, a new species of Baetidae (Ephemeroptera) from Costa Rica, Central America - Sibaja-Araya, Fabián; Esquivel, Carlos (Zootaxa, 2018)
The nymphs of a new species of Camelobaetidius (Ephemeroptera: Baetidae) possibly related to the South American species of this genus were found on the Atlantic and Pacific slopes of Costa Rica. Among other characteristics it is distinguished by having the anterodorsal arc of labrum with 1 + 6 setae, the first two frayed, ventrally 4 small setae near the lateral margin, and a minute seta near the anterior margin, on both sides of the cleft; the left mandible incisors with 6 denticles similar in size and the tip of the slender process extended at about the same level as the incisors; the paraglossa and glossa equal in length and a little shorter than segment II of labial palp, and a short triangular distomedial projection on segment II of labial palp; small nipple-like thoracic gills at base of forecoxa; claws with 27–32 denticles; posterior margin of abdominal terga with rounded spines; paraproct with 1–3 sclerotized spines, and cerci approximately 12% longer than the median filament. Both sexes present several different colorations. Some data on microhabitat preferences of nymphs are also given.